2018
DOI: 10.1177/1060028018782209
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Epoprostenol Through Noninvasive Routes of Ventilator Support Systems

Abstract: A total of 36 patients received iEPO through noninvasive routes: high-flow oxygen therapy through nasal cannula, n = 29 (81%) and noninvasive positive-pressure ventilation, n = 7 (19%). Sixteen patients had improvement in their respiratory status: mean decrease in fraction of inspired oxygen (FiO), 20% ± 13%; mean increase in partial pressure of arterial oxygen to FiO (PaO/FiO) ratio, 60 ± 50 mm Hg; and mean decrease in HFNC oxygen flow rate, 6 ± 3 liters per minute (LPM). Eight patients had declines in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
(52 reference statements)
2
28
1
Order By: Relevance
“…In this study, however, we found a trend of higher response rate in the group with flow titration (63.6% vs. 38.5%) (Table 5). Similarly, Ammar et al reported a mPAP reduction of 4.9 ± 6.2 mmHg after iEPO via HFNC in 9 patients with pulmonary hypertension using constant flow [9], this finding is consistent with the constant flow group (4.2 ± 3.9 mmHg) but lower than the mPAP reduction in the flow titration group (9.3 ± 6.3 mmHg) in our study. Additionally, the percentage of responders who had mPAP reduction of greater than 20% was higher in the flow titration group (46.2% vs. 0, p = 0.046).…”
Section: Clinical Impact Of Flow Titration For Iepo Delivery Via Hfncsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, however, we found a trend of higher response rate in the group with flow titration (63.6% vs. 38.5%) (Table 5). Similarly, Ammar et al reported a mPAP reduction of 4.9 ± 6.2 mmHg after iEPO via HFNC in 9 patients with pulmonary hypertension using constant flow [9], this finding is consistent with the constant flow group (4.2 ± 3.9 mmHg) but lower than the mPAP reduction in the flow titration group (9.3 ± 6.3 mmHg) in our study. Additionally, the percentage of responders who had mPAP reduction of greater than 20% was higher in the flow titration group (46.2% vs. 0, p = 0.046).…”
Section: Clinical Impact Of Flow Titration For Iepo Delivery Via Hfncsupporting
confidence: 91%
“…SpO 2 /F I O 2 was substituted for PaO 2 /F I O 2 to evaluate oxygenation [8,16] in cases where arterial blood gases before and after iEPO initiation were not available. A patient was also considered a responder to iEPO if SpO 2 /F I O 2 increased by > 20% for ≥ 5 min or PaO 2 /F I O 2 increased by > 20% within 60 min of iEPO initiation [8,9].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, aerosol delivery via high-flow nasal cannula (HFNC) has become a popular measure to deliver aerosol therapy [1][2][3][4][5][6][7][8], particularly for patients who are using HFNC concurrently [1][2][3][4][5]. At regular flow setting, trans-nasal albuterol delivery for stable patients with chronic obstructive airway diseases has been shown to elicit similar response as conventional nebulization treatment [6][7][8], such as small volume jet nebulizer via mask/mouthpiece or metered dose inhaler with spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its features of no additional gas and little to no residual volume, vibrating mesh nebulizer (VMN) has been commonly utilized in trans-nasal aerosol delivery [1][2][3][4][5][7][8][9]. However, the currently available commercial product of VMN generates aerosol continuously.…”
Section: Introductionmentioning
confidence: 99%